Teaching comparative religions in India through heritage - Punja, Shobita (Material religion, 2010)
This article is a case study of a program designed by INTACH for Teaching Comparative Religions and Heritage. The purpose of the program was to evolve a creative and educational experience for students to study the different faiths of India through the exploration of their artistic contributions in architecture, sculpture, painting, and music and other performing arts. The program resulted in the production of a film called Heritage and Harmony that is being used as a teaching aid for heritage education in INTACH teacher training program throughout India. In this film a group of students explore various tangible and intangible aspects of Islamic culture including philosophy, architecture, music, food, traditions, and festivals. The film depicts interesting ways to study heritage through walks with an expert to a monument or museum, interviews and discussion with members of the local community, workshops on a craft or living tradition (painting, calligraphy, music, dance, etc.), recording information, creative writing and poetry exercises, drawing, photography, and film making. The experiment in making a film on comparative religions and heritage education proved to be informative. It was clear that students in India wanted to know more about the world, other religions, and philosophies. The multidisciplinary approach appealed to the different abilities and talents of students. Most important students commented that this program had offered them their first, real experience in understanding the cultural context in which they live.